Efficacy of Sulfuryl Fluoride as a Fumigant against Aspergillus niger on Corn Seeds - Leny Panjaitan; Salbiah Salbiah; Ranta Hadi; Abdurakhman Abdurakhman; Mustopha Ahad (Jurnal Perlindungan Tanaman Indonesia, 2020)
The importation of corn seeds may inadvertently introduce seed-borne fungi like Aspergillus niger. One potential method to control this pathogen was fumigation with sulfuryl fluoride. The objectives of this applied research were to obtain effective concentration and exposure time of sulfuryl flouride as a fumigant to control seedborne fungi and to its physiological impact on corn seeds. Aspergillus niger was isolated from corn seed samples, grew it in potato dextrose agar, and used it for in vitro studies. Parameters  observed were isolates’ growth inhibition. In vivo studies were conducted using corn seed samples infected by Aspergillus niger. Sulfuryl fluoride was applied at the concentration of 30, 40, 50, and 60 g/m3 and 24, 48, 72, and 96 hour of exposure time. Results showed that sulfuryl fluoride concentration of 40 g/m3 for 48 hours at 26-32°C is the only effective concentration against A. niger in vitro but all of the treatment did not significantly affect A. niger in vivo. Concentration of 30, 40, 50, 60 g/m3 for 24 hours does not affect the quality of the seed.